IMPROVING ECOLOGICAL CULTURE IN PRIMARY STUDENTS METHODOLOGY - Uljamol Shermatova (Journals Park Publishing, 2025)
This article highlights methodological approaches to the formation and improvement of ecological culture among primary school students. Against the backdrop of increasing environmental problems, fostering ecological awareness, responsibility, and behavior in the younger generation has become one of the urgent pedagogical tasks. The article analyzes the role of innovative methods, practical exercises, game-based activities, and extracurricular work in effectively organizing ecological education, taking into account the age-specific psychological and pedagogical characteristics of primary school students. The research findings justify the need for systematic and step-by-step development of ecological culture and offer practical recommendations for teachers.
Keywords: Primary school students, ecological culture, environmental education, methodological approaches, pedagogical process, practical exercises, game-based methods, extracurricular activities, ecological awareness, innovative methods, educational process, student upbringing.